THE EFFECT OF USING FORMULA APPROACH ON THE TEACHING OF MATHEMATICAL CONCEPTS IN SENIOR SECONDARY SCHOOLS IN KADUNA STATE - Kajuru, Y. K. (Sokoto Educational Review, 2020)
This research was a quasi-experimental study, which was carried out to see how formula approach as an instrumental strategy could enhance the performance of Senior Secondary School Students in Zaria Educational Zone of Kaduna State. Thirty four (34) Senior Secondary School Students in SS3 were used in this study in which seventeen (17) are males and seventeen are females. An experimental treatment was carried out in the experimental groups while the conventional approach was followed in the control group. The study revealed that formula approach if effectively administered will enhance better performance of the students in senior secondary schools. This is because, the students that were taught by the formula approach performed significantly better than those that were not. Similarly, the study was able to remove the much talked gender difference between males and females since there was no significant difference between the performances of the two groups.